Adolescentes infratores: estudo acerca da medida sócio-educativa de internação nas unidades do Centro de Atendimento Sócio Educativo ao Adolescente - CASA como defesa da cidadania - Worm, Naima (2007)
With the promulgation of the 1908 s Federal Constitution and the development of the Children and Adolescents Statute in 1990, a phase of rights celebrations and fundamental guarantees to all citizens have started in the country. In the same way, rights that guaranteed dignity to children and teenagers have been designed, moving them from a legal object condition to a legal subject one. This work is directed to a share of the young population, to the adolescents who committed an offense and are concealed in the Units of the Centre of Socio-Educational for Adolescents Care CASA in the district of São Paulo and the execution of rights and fundamental guarantees. This dissertation starts with a brief history of the beginning of rights of children and adolescents, contrasting the teenagers rights to the Federal Constitution. Following this first part, there is a study of socio-educational measures, their nature and legal grounds. An approach concerning the Doctrine in the Integral Protection to the native right is also part of this dissertation. Finally, and perhaps more important, field researches take place and three hundred and sixty male adolescents who were concealed in eighteen Units in the capital are interviewed in order to inquire if the law is being applied in real life conditions. The main aspects observed in the research were: the socioeconomic profile and the educational formation, the aspects related to the routine in the units as part of a formal education, the professionalizing courses and sports, cultural and pedagogical activities, and, at last, the security aspect, discipline and the teenager s fall backs.